Proteoglycan Sulphation in the Function of the Mature Central Nervous System - Fawcett, James W.; Kwok, Jessica C. F. (Frontiers in Integrative Neuroscience, 2022)
Chondroitin sulphate and heparan sulphate proteoglycans (CSPGS and HSPGs) are found throughout the central nervous system (CNS). CSPGs are ubiquitous in the diffuse extracellular matrix (ECM) between cells and are a major component of perineuronal nets (PNNs), the condensed ECM present around some neurons. HSPGs are more associated with the surface of neurons and glia, with synapses and in the PNNs. Both CSPGs and HSPGs consist of a protein core to which are attached repeating disaccharide chains modified by sulphation at various positions. The sequence of sulphation gives the chains a unique structure and local charge density. These sulphation codes govern the binding properties and biological effects of the proteoglycans. CSPGs are sulphated along their length, the main forms being 6- and 4-sulphated. In general, the chondroitin 4-sulphates are inhibitory to cell attachment and migration, while chondroitin 6-sulphates are more permissive. HSPGs tend to be sulphated in isolated motifs with un-sulphated regions in between. The sulphation patterns of HS motifs and of CS glycan chains govern their binding to the PTPsigma receptor and binding of many effector molecules to the proteoglycans, such as growth factors, morphogens, and molecules involved in neurodegenerative disease. Sulphation patterns change as a result of injury, inflammation and ageing. For CSPGs, attention has focussed on PNNs and their role in the control of plasticity and memory, and on the soluble CSPGs upregulated in glial scar tissue that can inhibit axon regeneration. HSPGs have key roles in development, regulating cell migration and axon growth. In the adult CNS, they have been associated with tau aggregation and amyloid-beta processing, synaptogenesis, growth factor signalling and as a component of the stem cell niche. These functions of CSPGs and HSPGs are strongly influenced by the pattern of sulphation of the glycan chains, the sulphation code. This review focuses on these sulphation patterns and their effects on the function of the mature CNS.